The quality assessment of information service of readers by librarians - E. V. Avramova (Библиосфера)
The paper examines relationships of the quality estimation of the reference-information service for readers by librarians with professional motivation. Study results are based on the questionnaire survey of 199 employees of the public libraries network in Saint Petersburg. The study has been done in frames of research project «Staff development of public libraries of the corporate network of public libraries in Saint Petersburg executing the information-bibliographic service» in 2013-2014.